Juridical cosmopolitanism as a condition for world peace : Overcoming the historical distance of the Kantian cosmopolitical legacy in Habermas - Zúchi, Tiago (Sofia, 2023)
The present article tries to make a relation between the cosmopolitanism thought by Kant and that revisited by Habermas, two centuries later. It will be seen that Kant grounded cosmopolitanism on a republican understanding of State; differently, Habermas bases it on a comprehensive international human rights law of all democratic constitutional State. Although there are theoretical differences between them, they fit into the purpose of the cosmopolitan project. For both, a universal society must embrace cosmopolitanism so that lasting peace can be assured. And since the Kantian cosmopolitan theory has proved insufficient over time, re-reading it through legal cosmopolitanism has become more attractive for achieving world peace in post-modern times.